BEGINNING VOTER'S VIEWS ON PARTY POLITICAL COMMUNICATION - Tidy Mutiara Lestari Sudarminto Putri; Martini; Nova Scorviana (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This research aims to discuss the perceptions of novice voters regarding the function of political parties as political communication. The research method used is qualitative with descriptive research type. This research data was collected by interviewing 7 informants consisting of first-time voters. The research results show that the views of novice voters regarding party political communication have not yet implemented the function of political parties as political communications. According to novice voters, political parties have conveyed political information regularly, but political parties have not been optimal in channeling people's aspirations. The political communication media that political parties often use in political communication is social media, so this makes it easier to disseminate information to the public. The suggestion from this research is that political parties must improve their performance by carrying out various functions properly. That way, people can trust political parties again.